Dynamics of Urban Arboviruses Transmitted by Aedes Aegypti in Brazil: Integrative Literature Review - , Kélia das Graças de Paiva Macias Nakai, Girlene Ferreira Quingosta, Tamara dos Santos Ferreira, Andressa Torres Oliveira, Danielle de Alencar Alves dos Santos Franco, Simone do Socorro de Souza Ribeiro, João Victor Moura Rosa, Wanessa Yasmin Silva Prado Carneiro, Lucilene Lima Sousa, Sandy Costa dos Santos, Larissa Karem Santos, Leonardo Silva da Costa; et al. (Archives of Current Research International, 2025)
Background: Urban arboviruses transmitted by Aedes aegypti represent a growing challenge for Brazilian public health, with significant impacts in terms of morbidity and mortality, overload of health services and socio-environmental inequalities. Objective: Analyze the dynamics of urban arboviruses transmitted in Brazil as a basis for more effective control actions. Method: This is an integrative literature review, with searches carried out in the SciELO, LILACS, PubMed and BVS databases, using descriptors such as “arboviruses”, “Aedes aegypti”, “dengue”, “chikungunya” and “Zika virus”. Complete articles in Portuguese, English and Spanish, published between 2018 and 2025, with a clinical, epidemiological, environmental or political focus were included. Data analysis was performed through thematic categorization. Results: Twenty-three studies were selected and organized into five categories: epidemiological patterns; environmental and climatic conditions; epidemiological surveillance and monitoring technologies; clinical aspects and complications; and prevention and control strategies. A progressive increase in cases, influence of socio-environmental factors, limitations in surveillance, clinical severity and weaknesses in the implementation of public policies were observed. Conclusion: The analysis indicates that the persistence of arboviruses in Brazil results from the interaction between structural failures and a fragmented institutional response. It concludes that strengthening epidemiological surveillance, combined with the integration of sustainable, evidence-based public policies, is essential to reducing the impact of these diseases.